2021
DOI: 10.1039/d0mh01380c
|View full text |Cite
|
Sign up to set email alerts
|

Approaching “stainless magnesium” by Ca micro-alloying

Abstract: Highly corrosion-resistant Mg is readily achievable by Ca micro-alloying, making “stainless Mg” possible. The designed lean Mg–Ca holds great promise in diverse applications, particularly biodegradable medical implants and aqueous batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 39 publications
0
21
0
2
Order By: Relevance
“…However, the alloying design can slow the degradation rate by an order of magnitude or more, which may still not be sufficient for many applications. There are reports in the literature that micro-alloying and amorphous Mg-based glasses can further inhibit the degradation rate of Mg-based materials [ [248] , [249] , [250] ]. Regarding Mg-based metallic glasses, their single-phase structure and chemical homogeneity can minimize the galvanic corrosion effect [ 65 ].…”
Section: Comparison and Challenge In Functionalized Coatings On Mg Alloy Stentsmentioning
confidence: 99%
“…However, the alloying design can slow the degradation rate by an order of magnitude or more, which may still not be sufficient for many applications. There are reports in the literature that micro-alloying and amorphous Mg-based glasses can further inhibit the degradation rate of Mg-based materials [ [248] , [249] , [250] ]. Regarding Mg-based metallic glasses, their single-phase structure and chemical homogeneity can minimize the galvanic corrosion effect [ 65 ].…”
Section: Comparison and Challenge In Functionalized Coatings On Mg Alloy Stentsmentioning
confidence: 99%
“…Furthermore, alloying can enhance other properties such as corrosion and degradation. 55 , 56 Rationally combining elements for stability and plasmonic response may be a way to stabilize the reactive group I metals and instill some of their low losses and high quality resonances into another metal; such promising nanostructures have yet to be reported. Overall, while there is a limited track record of drastic improvements in plasmonic quality due to the fundamental nature of the materials, a new discovery that would dramatically change the quality factor has the potential to propel plasmonics to a new era.…”
Section: Discussionmentioning
confidence: 99%
“…When a small amount of Nd 17 or Y/Ca 18 was added into AZ91-series alloy, the corrosion rate can be alleviated through reducing the potential difference between the secondary phases and the magnesium matrix. Another recent study 19 indicated that trace addition of Ca into ultra-pure magnesium could slow down the corrosion rate by controlling impurities and inducing a protective film. Whilst the corrosion resistance of the abovementioned alloys 17 19 is marginally better than HP-Mg, their mechanical properties are far from satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study 19 indicated that trace addition of Ca into ultra-pure magnesium could slow down the corrosion rate by controlling impurities and inducing a protective film. Whilst the corrosion resistance of the abovementioned alloys 17 19 is marginally better than HP-Mg, their mechanical properties are far from satisfaction.…”
Section: Introductionmentioning
confidence: 99%